Contribuição do ensino de Filosofia para a formação autônoma e emancipada de alunos do Ensino Médio - Formiga, Jean Carlos Dantas (2020)
The proposal of this master's dissertation with the title THE CONTRIBUTION OF PHILOSOPHY TEACHING TO AUTONOMOUS AND EMANCIPATED STUDENT TRAINING IN HIGH SCHOOL sought inspiration and theoretical basis in the thinking of the philosophers Immanuel Kant and Theodor Adorno, revisiting some of his works so that we could find the theoretical support that leads to an education, through the teaching of Philosophy, capable of promoting an autonomous and emancipated formation of students. Thus, the research aims to reflect on Philosophy in High School as an autonomous and enlightened training space, investigating through an epistemological inductive process, justified by the set of interventions (observation and questionnaire application) the perception of students in public schools Fortaleza - CE on the teaching of this discipline. For the analysis of the data, a phenomenological analysis was carried out, highlighting that it is not intended to insert this view only in the subjective questions, but also for the statistical data presented, therefore not limiting itself in quantifying them, observing also how it has been worked in the classroom. By focusing on the empirical part of the research, we could see that, although with some difficulties in terms of time, appreciation, importance, etc., the Philosophy classes in High School bring a contribution to the autonomous and emancipated training of students since they themselves were clear when affirming how much the opportunity that the teaching of Philosophy brings them to develop critical and reflective thinking and, therefore, autonomous and enlightened, still giving them discernments in their choices regarding their actions, the understanding of their existence and of the society where they live. Finally, all respondents agreed that the discipline contributes to their autonomy and emancipation. In our final remarks, we highlight that the Philosophy Discipline in High School and the actions of teachers in this discipline are not only preludes to a major public transformation project, but, in fact, are themselves continuous with and in that same transformation. Thus, the need for change, which is the greatest challenge in education, responds to this urgent demand, highlighting the subjects - students and teachers of Philosophy teaching - as co-participants in the construction of their knowledge and social transformation.